Writing for publication: avoiding the common pitfalls - Leslie Gelling (Nurses and Midwives Association of Slovenia, 2017)
Sharing research findings has become an increasingly important part of research as nursing is increasing required to base practice on the best available evidence. This editorial offers an insight into some of the common pitfalls to avoid when writing and submitting a paper for publication.